Infrastructure, Modernity, and the Technologies of Everyday Life: Insights from a Collaborative Research Project on the Making of Modern East Asia. Issue 3 (1st September 2020) - Hirsh, Max; Leung, Angela Ki Che; Nakayama, Izumi
Abstract: The article shares key insights gleaned from a multiyear collaborative research project on the role of everyday technologies in the making of modern East Asia from the nineteenth century to the present. It explains the three key concepts that have guided the authors' collective research on technological processes and modernity—East Asia as a region, infrastructure, and the everyday—illustrating each with specific examples drawn from the domains of food, childbirth, pharmaceuticals, transportation, automation, weather forecasting, and telecommunication. In so doing, the project seeks to introduce two innovations into the study of East Asian science and technology. From a conceptual perspective, the authors' emphasis on infrastructure introduces new lines of inquiry into the various types of networks through which technical changes are conceived, produced, and disseminated. At the same time, the authors' focus on the everyday traces how those technologies have been mixed, modified, and adapted by end users in accordance with culturally specific norms, needs, and aspirations. Moreover, by foregrounding collaborative forms of research, the project advances new methodological strategies into the study of technology and its knowledge, practice, and artifacts that define and redefine East Asia as a region with fluid boundaries.